Two new species of Sphaeronemoura (Plecoptera: Nemouridae) from Yunnan Province of China - Qian, Yu-Han; Fu, Li; Jiao, Jun-Ying; Du, Yu-Zhou (Zootaxa, 2019)
Two new species of the nemourid genus Sphaeronemoura are described based on males and females collected from Yunnan Province of southwestern China. The new taxa include S. kunmingensis Qian & Du sp. nov. and S. campylura Qian & Du sp. nov.. The new species are compared to related taxa.